Fisikawaii Adventure: An Effort to Increase Students' Learning Participation through Gamification and Virtual Reality - M Vithor Al Faqih; Anggi Widiarni; Nisa Andini; Antomi Saregar; Sergii Sharov; Bawar Mohammed Faraj (CV FOUNDAE, 2023)
Student participation is critical in education. Technology integration, such as virtual reality, enhances the visualisation of physics concepts and participation. Combining virtual reality and gamification creates an immersive and interactive learning experience. This research aims to design and implement a learning management system (LMS) called Fisikawaii Adventure integrated with gamification and virtual reality. This study follows the ADDIE (Analysis, Design, Development, Implementation and Evaluation) development model. The motivational element of GAFCC (Goal, Access, Feedback, Challenge, and Collaboration) was employed in the design stage. The LMS was evaluated at SMAN 2 Bandar Lampung with ten eleventh-grade MIPA (Mathematics and Natural Science) students. The data collection technique employed was a non-test instrument. The data analysis technique was qualitative-quantitative using the Likert scale. Fisikawaii Adventure was valid with an average percentage score of 85.5 from material experts, 87.25 from media experts, and 86.4 from student responses (very feasible category). The product was feasible to use in physics learning and increase students' participation. Although it requires further investigation, this research contributes significantly to integrating gamification and virtual reality into LMS and physics learning.